Implementasi Pembelajaran Fikih Lokal di MA Tanbihul Ghofilin, Bawang, Banjarnegara - isma, Isma Kholifatun Hikmah; Darin, Abu (Lembaga Penelitian dan Pengabdian Masyarakat STAI Brebes, 2025)
The times require the younger generation to adapt, including in solving fiqh issues that continue to grow. The younger generation is expected to be able to play an active role as a successor to religious figures in society. This study aims to examine the implementation of local fiqh learning at MA Tanbihul Ghofilin, Bawang, Banjarnegara. The focus of the research includes the understanding of local fiqh, material sources, curriculum, learning process (preparation, implementation, evaluation), as well as the benefits for students. This research uses a field research method with a qualitative descriptive approach. The data collection methods used by researchers were observation, interviews, and documentation. The data validity method is through data tringulation which combines the results of interviews, observations, and or documentation. The data analysis method uses Miles and Hubermen's interactive analysis which is reviewed including data collection, data reduction, data presentation, and conclusion drawing. The results showed that: 1) Local Fikih subject is fiqh learning that uses source material from the book of Fathul Qorib with the pesantren method (bandongan) and focuses on the application of fiqh law in everyday life. 2) The stages of local fiqh learning include preparation, implementation, and evaluation. 4) This learning is considered important because students are given a place to understand fiqh learning in depth, as a provision to answer fiqh problems in society that continue to grow.